2021
DOI: 10.1038/s41598-021-93023-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the catalytic activities of methanol and thermotolerant Kocuria flava lipases for biodiesel production from cooking oil wastes

Abstract: In this study, two highly thermotolerant and methanol-tolerant lipase-producing bacteria were isolated from cooking oil and they exhibited a high number of catalytic lipase activities recording 18.65 ± 0.68 U/mL and 13.14 ± 0.03 U/mL, respectively. Bacterial isolates were identified according to phenotypic and genotypic 16S rRNA characterization as Kocuria flava ASU5 (MT919305) and Bacillus circulans ASU11 (MT919306). Lipases produced from Kocuria flava ASU5 showed the highest methanol tolerance, recording 98.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 96 publications
1
6
2
Order By: Relevance
“…The FTIR analysis showed a peak at 1735.17 cm −1 , which confirmed the production of biodiesel. The results of this study agreed with the findings of Najjar et al (Najjar et al 2021 ) who reported produced biodiesel has showed an absorption band at 1743 cm −1 by (FTIR).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The FTIR analysis showed a peak at 1735.17 cm −1 , which confirmed the production of biodiesel. The results of this study agreed with the findings of Najjar et al (Najjar et al 2021 ) who reported produced biodiesel has showed an absorption band at 1743 cm −1 by (FTIR).…”
Section: Discussionsupporting
confidence: 93%
“…However, low growth was observed at 15% methanol concentration at 24, 48, and 72 h at 37 °C. Other study results obtained for the lipase enzyme activity of microbes also showed that, there was a sharp reduction at higher concentrations of methanol (Najjar et al 2021 ). The current results depicted that although the growth was reduced at higher concentrations of methanol, strain Q4 was not completely inhibited or killed by methanol.…”
Section: Discussionmentioning
confidence: 75%
“…The results showed that the whole-cells lipase from M. spicifer preferred branched alcohol (2-butanol and iso-butanol) to the linear ones (methanol, ethanol, propanol and 1-butanol). The results were not in agreement with the previously reported, in which methanol was more favorable than the longer-chain alcohols for whole-cells lipases developed from Rhodotorula mucilaginosa [10], Kocuria flava ASU5 [25] and Bacillus circulans ASU11 [25]. Moreover, the biodiesel production using longer and branched chain length alcohol provided product advantages of low temperature performance, which is important when using diesel engines in winter or cold climates [33].…”
Section: Effects Of Acyl Acceptor On Synthesis Of Fatty Acid Alkyl Es...contrasting
confidence: 74%
“…Correspondingly, an initial pH of 5 was found to be the optimum for CBL activity of M. spicifer SPB2 in this study. However, pH showed no significant in lipase production for Kocuria flava [15,25]. Carbon sources displayed to be less influent than nitrogen sources and surfactants on hydrolytic CBL production of M. spicifer SPB2.…”
Section: Optimization Of Culture Medium For Improvement Of Hydrolytic...mentioning
confidence: 87%
“…The oven temperature was 80 • C for 5 min, then the temperature was increased at the rate of 10 • C min −1 to 150 • C and 200 • C for 10 min each, and finally, the oven temperature was raised at an increasing rate of 5 • C min −1 to 250 • C for 13 min. The injector temperature was 250 • C and the detector temperature was 300 • C. The percent of FAMEs yield was estimated by comparison with the peak area of internal standards at the specific retention time [40].…”
Section: Biodiesel Production From Microbial Lipids Chemicallymentioning
confidence: 99%